Device Closure of Patent Ductus Arteriosus in Adults - Adhikari, Chandra Mani; Timalsena, Birat Krishna; Shah, Subash; Shrestha, Manish; Prajapati, Dipanker (Journal of National Heart and Lung Society Nepal, 2026)
Patent ductus arteriosus (PDA) persisting into adulthood is an uncommon but clinically significant congenital heart condition, representing the third most common congenital cardiac lesion in adults. Clinical presentation varies widely, from asymptomatic cases with incidental murmurs to complications such as left ventricular (LV) volume overload, pulmonary arterial hypertension(PAH), endarteritis, and Eisenmenger physiology. Classification is based on duct size and hemodynamic impact, guiding management decisions. Untreated PDA in adults carries risks including arrhythmias, LV dysfunction, progressive PAH, and endarteritis, which remains a leading cause of mortality. Current guidelines recommend closure when technically feasible, particularly in the presence of LV overload or favorable pulmonary vascular resistance.While surgical closure was historically the gold standard, transcatheter device closure is now the first-line treatment due to lower morbidity, shorter recovery, and high success rates. However, adult PDA closure presents unique challenges, including calcification, tortuosity, and complex anatomy, necessitating precise imaging and appropriate device sizing. Complications such as device embolization, residual shunt, and LV dysfunction may occur but are infrequent.